MANAJEMEN ASUHAN KEBIDANAN BERKELANJUTAN POST NATAL PADA NY”W” DENGAN BENDUNGAN ASI HARI KETIGA SAMPAI 31 HARI MASA NIFAS DI PUSKESMAS BARA BARAYA - Raditha Nur Arsy Jamaruddin S; Ferawati Taherong; Syatirah (Prodi Kebidanan Universitas Islam Negeri Alauddin Makassar, 2022)
Introduction Breast milk dam is the accumulation of milk in the breast due to narrowing of the lactiferous ducts or glands that are not completely emptied during babies’ breastfeeding. It could also occur because of the abnormalities in the nipples of mothers. Breast milk dams usually be found on the third to fifth day after a delivery. The major purpose of this scientific paper was to investigate and implement a sustainable midwifery care management for Mrs